Pembangunan dan Pendampingan Sosialisasi Asuhan Mandiri Tanaman Obat Keluarga (Asman Toga) di Dusun Gondek, Kabupaten Jombang Oleh Peserta KKN-T UPN Jatim - Abrorurizal Ladooney; Agus Dwiyanto; Muhammad Raihan Adji; Daniel Ramadhan; Roziana Febrianita (Institut Nalanda, 2024)
The social work program is one of the policies for students, real work lectures (KKN) are a form of social work. Special care for family plants (ASMANTOGA) is something new for the people of Gondek Village, Mojowarno District, Jumbang District, especially in Gondek Hamlet itself. However, Gondek hamlet itself still does not have ASMAN TOGA land. In community service in Gondek village, they built land for ASMAN TOGA, which is precisely in Gondek hamlet. The construction of the ASMANTOGA park aims to provide a little information about the benefits of plants and also that the people in Gondek village have knowledge about these plants. Implementation is carried out using several methods, namely planning, preparation, observation, implementation, delivery, evaluation, monitoring of results. The result of this activity is the development of the ASMAN TOGA land and the introduction of QR-Code digital information. It is hoped that the results of this activity can provide benefits and increase public education in utilizing medicinal plants in ASMAN TOGA Park.